Application of the Fuzzy Logic Method in Determining the Volume of Water Discharge to the Number of Humans Based on a Microcontroller - Muhammad Furqon Siregar; Chairul Imam (Journal of Science Technology (JoSTec), 2022)
This research discusses the implementation of fuzzy logic in the design of an automatic water valve system. Fuzzy logic is used to calculate input values to avoid inappropriate power due to excessive sensor input variations. The system performance assessed is the success of the system in regulating the number of people at the capacity of water volume availability. The sensor system detects the number of people entering to determine the capacity according to the given input. The system is designed using an ATmega328 microcontroller. Ultrasonic & PIR sensors are used to predict the number of people passing by the door. To evaluate the performance of the system, the maximum number of 800 people, to avoid system failure. Experiments showed better accuracy in determining the degree of rotation of potentials and relays when the Tsukamoto fuzzy logic model was implemented. The system is more stable and the average value obtained is 34.1%.